Site-Specific Art Installation: Ruang Masuk ArtJog “Arts in Common” di Jogja National Museum - Elfandi, Amy; Kurniawan, Harry (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2025)
Title: Site-Specific Art Installation; Entrance of ArtJog “Arts in Common” at Jogja National Museum The art installation serves as an object that fills a space in a building, an imaginary space, or a space in the open air. The installation possesses aesthetic characteristics that defy rigid boundaries in fine art, which are typically considered standard, and it also lacks limitations in the use of media or materials. ArtJog is one of the premier art exhibition events in Yogyakarta, featuring art installations. ArtJog originated from art fairs that always featured a central art installation placed at the entrance, using a concept or theme in line with the ongoing exhibition. ArtJog art installations are non-permanent, so that the exhibition space will be dismantled upon the exhibition's conclusion. The main art installation work at the entrance is essential as an application of the concept and theme that means